THE IMPLICATION OF PARADIGMATIC AND SYNTAGMATIC RELATIONS IN MORPHOLOGY TO LANGUAGE TEACHING AND LEARNING: A SYSTEMATIC OVERVIEW - Aisyah; Despita; M. Bambang Purwanto (Language and Education Journal, 2024)
English Language has many unique properties among which are words; the most tangible elements of a language. Morphology has an impact on Language learners’ ability to both listen and speak efficiently in English. Indeed, the most serious problems of teaching English have to do with the quality of the teachers available for teaching the language as nearly all such teachers are L2 speakers. The paper aims to broaden the scope and knowledge of students and their teachers on word use and word formation through paradigmatic and syntagmatic relations. Accordingly, the possibility of effecting appreciable improvement in the quality of the English spoken in the country as a whole would appear very remote if the study of words and their relationships continue to be neglected in schools. The paper recommends the training of teachers in Contractive Linguistics who are unable to understand and consequently devise effective pedagogical strategies for combating the mostlymother-tongue-induced kinds of learners' errors that recur in students' written and oral performances in the language